2023
DOI: 10.3390/jcm12020576
|View full text |Cite
|
Sign up to set email alerts
|

Spring Plates as a Valid Additional Fixation in Comminuted Posterior Wall Acetabular Fractures: A Retrospective Multicenter Study

Abstract: Background: The posterior wall fracture is the most frequent pattern of acetabular fractures. Many techniques of fixation have been described in the literature and involve plates, screws, or a combination of both. This study aims to investigate the clinical and radiological outcomes of spring plates in the treatment of comminuted posterior wall acetabular fractures. (2) Methods: A retrospective multicenter (four level I trauma centers) observational study was performed. Patients with a comminuted posterior wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In a study by De Mauro et al involving 46 patients, successful results were obtained using Spring plates and it was concluded that these plates can be used as additional support in posterior fractures. [18] In cases where suprapectineal and/or infrapectineal plate fixation may not be sufficient to preserve the reduction of the QLS, we used interfragmentary screws or square bracket-shaped tubular plates to conserve the reduction in addition to suprapectineal and/or infrapectineal reconstruction plate fixation. [14] In comminuted fractures of the QLS, an infrapectineal plate is usually placed using a modified Stoppa approach to reconstruct the QLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by De Mauro et al involving 46 patients, successful results were obtained using Spring plates and it was concluded that these plates can be used as additional support in posterior fractures. [18] In cases where suprapectineal and/or infrapectineal plate fixation may not be sufficient to preserve the reduction of the QLS, we used interfragmentary screws or square bracket-shaped tubular plates to conserve the reduction in addition to suprapectineal and/or infrapectineal reconstruction plate fixation. [14] In comminuted fractures of the QLS, an infrapectineal plate is usually placed using a modified Stoppa approach to reconstruct the QLS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by De Mauro et al involving 46 patients, successful results were obtained using Spring plates and it was concluded that these plates can be used as additional support in posterior fractures. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The correct outcome to evaluate the risk of septic failures was chosen according to the data found in the Literature. First endpoint was to assess periprosthetic joint infection rates, considering it as the mean diagnosis when it comes to septic complications [ 29 ]. Surgical site infections, instead, were less related to actual septic failure, but the available data allowed us to use this information to better define the impact of bariatric surgery as prevention of infections in joint arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies ( 15 , 27 ) did not report neither malunion nor nerve impairment after surgery. The main limitation of TOS technique is that it requires a highly skilled surgeon specialized in the treatment of pelvic ring fractures as it is a very complicated procedure ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%